Meningkatkan Kinerja Keuangan melalui Intellectual Capital: Bukti Empiris Perusahaan Otomotif Bursa Efek Indonesia - Dhani Ichsanuddin Nur (Jurnal Aplikasi Manajemen, 2012)
The Growth of  profit depends on the financial condition or company financial performance. The better the company work performance, the bigger profit the company will get. This research is intended for knowing the influence of capital intellectual on company finanacial performance. The sampling technique is using purposive sampling from automotive company registered in Bursa Efek Indonesia period 2002 - 2006 using secondary data. Analysis data is processed using double linear analysis then followed by hypothesis test. The result of the research shows that capital employee efficiency  has insignificant positive influence on financial performance, human capital efficiency has insignificant positive influence on financial performance, and structural capital efficiency  has insignificant negative influence on financial performance of automotive company registered in Bursa Efek Indonesia.Keyword: capital employee efficiency, human capital efficiency, financial performance